To Die For: Modern Femininity and the Quest for Anti-Hegemonic Anthropomorphization - Kather, Cara-Julie (Journal of Ecohumanism, 2024)
This paper provides an analysis of how the concept of femininity is used in literary anthropormorphizations of animals and plants. I argue that this usage of femininity for anthropormorphization provides a framework from which animal and plant life are reevaluated as meaningful. However, the notion of femininity portrayed in my exemplary case study can be shown to depict a specifically white and patriarchal narration of femininity. Therefore, this paper explores possibilities for literary anthropormorphization that is feminist, decolonial and narrates animal and plant life as meaningful. My general advocacy is one for intersectional perspectives and new ways of generating meaning and worth that consider different, interwoven struggles at once and make sense of them precisely in their interwovenness. To do so I connect feminist literary criticism, decolonial theory, Afropessimism, and environmentalist perspectives. My case studies are the Song of the Dodo by David Quammen and Mushrooms by Sylvia Plath.